Peningkatan Keterampilan Menulis Prosa Deskriptif Melalui Model Quantum Learning - Trisusilawati Trisusilawati (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This study aims to improve the skills of writing descriptive essays by applying the quantum learning model. The research design used classroom action research with planning, implementing, observing, and reflecting stages. The location of this research is in class IX-A SMP Muhammadiyah Buntok, South Barito Regency, Central Kalimantan Province. The number of students in class IX-A SMP Muhammadiyah Buntok is as many as 18 people consisting of 8 boys and ten girls. The variables of this research are students' activities and students' writing skills. Data collection techniques using test techniques, observation, field notes, and documentation. This research consists of 2 cycles. The data was processed using quantitative and qualitative descriptive analysis techniques. The results showed that the student activity score in the first cycle was 66.66% in the sufficient category, and in the second cycle, it was 80.55% in the good class. While the percentage of mastery learning outcomes in the first cycle was 75%, and in the second cycle, it was 88.88. %. The conclusion is that the application of the Quantum Learning model can improve descriptive prose writing skills, including student activities and student learning outcomes in class IX-A SMP Muhammadiyah